2012
DOI: 10.3136/fstr.18.7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanofiltration to Recover Benzoic Acid from Cranberry Juice

Abstract: In this study, the feasibility of the application of nanofiltration to recover excess benzoic acid from cranberry juice was investigated. Different kinds of commercial nanofiltration membranes were screened for their ability to separate benzoic acid from cranberry juice. There were 7 kinds of membranes, including HC50, NFT50, G5, Desal-DK, DRA4510, UTC60 and NTR7250, which showed significantly lower rejection of benzoic acid than that of other components in cranberry juice, such as sugars, other organic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…From the previous studies, the conditions were selected as follows: the nanofiltration of cranberry juice was operated as concentration mode with total recirculation of retentate under the conditions as follows: feed flow rate: 6 L/min, operating temperature: 25 °C, operating pressure: 4 MPa (Lai et al ., 2012, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous studies, the conditions were selected as follows: the nanofiltration of cranberry juice was operated as concentration mode with total recirculation of retentate under the conditions as follows: feed flow rate: 6 L/min, operating temperature: 25 °C, operating pressure: 4 MPa (Lai et al ., 2012, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research evaluated the separation of benzoic acid in cranberry juice using different kinds of commercial nanofiltration membranes from dead‐end bench to cross‐flow pilot scale equipment under various operating conditions. The impact of operating conditions and UF pretreatment on cranberry juice NF was investigated in total recirculation mode (Lai et al ., 2012, 2021). In this study, the effects of UF pretreatment on cranberry juice NF were also investigated to improve the filtration process under concentration mode (total recirculation of retentate).…”
Section: Introductionmentioning
confidence: 99%
“…Figs. 3 and 4 illustrate retention ratio profiles of the compounds against solution pH (3)(4)(5)(6)(7)(8)(9) with the membranes. Retentions of the compounds by ES-20 and NTR-759HR (Fig.…”
Section: Retention Of Pfcsmentioning
confidence: 99%
“…Membrane separation is an outstanding method for eliminating a wide range of organic and inorganic constituents in water and wastewater treatments [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has indicated that benzoic acid can be significantly separated from cranberry juice by nanofiltration with a dead-end bench scale system [ 15 ]. In this work, the influence of technological parameters, (including the feed flow rate, temperature, pH, and operation pressure) on the separation of benzoic acid from cranberry juice by cross-flow nanofiltration is focused with a cross-flow pilot scale system.…”
Section: Introductionmentioning
confidence: 99%